2011
DOI: 10.1002/hbm.21407
|View full text |Cite
|
Sign up to set email alerts
|

Parieto‐frontal network in humans studied by cortico‐cortical evoked potential

Abstract: Parieto-frontal network is essential for sensorimotor integration in various complex behaviors, and its disruption is associated with pathophysiology of apraxia and visuo-spatial disorders. Despite advances in knowledge regarding specialized cortical areas for various sensorimotor transformations, little is known about the underlying cortico-cortical connectivity in humans. We investigated inter-areal connections of the lateral parieto-frontal network in vivo by means of cortico-cortical evoked potentials (CCE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 94 publications
5
78
1
Order By: Relevance
“…Our recent studies favor the direct cortico-cortical connection. The parieto-frontal CCEP connectivity study showed a linear correlation between the N1 peak latency and the surface distance from the parietal stimulus site to the frontal maximum response site (Figure 1A) [30]. This observation favors the direct cortico-cortical white matter pathway, because the longer the surface distance is, the proportionally longer the actual white matter pathway connecting the two cortical sites and, accordingly, its traveling time is.…”
Section: Ccep Methodologymentioning
confidence: 96%
“…Our recent studies favor the direct cortico-cortical connection. The parieto-frontal CCEP connectivity study showed a linear correlation between the N1 peak latency and the surface distance from the parietal stimulus site to the frontal maximum response site (Figure 1A) [30]. This observation favors the direct cortico-cortical white matter pathway, because the longer the surface distance is, the proportionally longer the actual white matter pathway connecting the two cortical sites and, accordingly, its traveling time is.…”
Section: Ccep Methodologymentioning
confidence: 96%
“…A left EOG electrode placed 2.5 cm below and 2.5 cm lateral to the left outer canthus showed a small signal deflection (Supplementary Figure S1). A previous human study using cortico-cortical evoked potentials suggested cortico-cortical propagation to be as rapid as 40 ms per 10 cm (Matsumoto et al, 2012), whereas the distance between the lower-order visual cortex and the orbitofrontal cortex is about 15 cm (Thiebaut de Schotten et al, 2012). Taken together, we failed to collect external evidence supporting that the orbitofrontal cortex receives ‘macroelectrode-detectable’ signals triggered by the lower-order visual cortex as rapidly as 130 ms following the image presentation.…”
Section: Discussionmentioning
confidence: 99%
“…CCEPs obtained with standard ('macro-') ECoG electrodes are increasingly utilized to probe cortical connectivity, such as in the human language, motor cortex, and frontal/parietal networks [7][8][9], or subcortical structures [13], as well as to explore pathological connectivity in epilepsy [17]. As they are perturbation-based, CCEPs can unequivocally show directed (causal) connectivity between remote areas [11,12], which is challenging to achieve by analysis of undisturbed brain dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…This well-established method allows one to unravel functional connectivity in the cortex [7][8][9][10][11][12] or subcortical regions [13], and recent studies used ECoG-based SPES in humans to investigate CCEPassociated changes in the spectral domain [14,15]. For reviews on studies investigating cortical connectivity by means of CCEPs see [16,17].…”
Section: μEcog Electrode Array Implant and Implantation Proceduresmentioning
confidence: 99%